Modeling the Sanitary Limit Between Water Wells and Latrines in the Equatorial Area, Cameroon Using Statistical and GIS Techniques - Djousse, B.M.K.; Teikeu, W.A.; Njeudjang, K.; Arétouyap, Z.; Assembe, S.P.; Njandjock, N.P. (Journal of Environmental Accounting and Management, 2026)
The availability of clean water and adequate sanitation facilities are of prime importance for limiting diseases. This study was conducted in the Yaoundé city (equatorial region), Cameroon which, experiences water supply limitations. The populations there in rely on domestic wells for drinking water. The objective was to define the sanitary limit for domestic drinking water wells using multiple linear regression and geographic information system techniques. Firstly, the water quality index (WQI) is calculated for 73 wells analyzed by the relative weight method knowing the measured values of groundwater chemical parameters. Secondly, the WQI values were then estimated and the validation step between the calculated and estimated value gives the coefficient of determination R^2=0.83. The Pearson’s correlation shows that hydraulic conductivity, groundwater depth and distance between water wells and latrines were significant parameters for assessing groundwater quality. Finally, multiple linear regression analysis is used to construct the map of the sanitary limit with the independent variables (hydraulic conductivity, groundwater depth and WQI = 25, the average value for excellent water quality) as input parameters. The map of sanitary limit shows that the values vary between 86 m and 170 m and can be used by practitioners for sustainable management of the water resources in this study area.